Re-integration, rehabilitation and return-to-work of disabled workers : a comparative legal enquiry - Gresse, E. (North-West University, 2020)
There are many employment positions in the labour market that could be filled by the disabled of whom most, given the right environment, could be productive in the workplace. However, there are employers who still labour under the misconception that Persons with Disabilities (PWDs) are unqualified and unproductive although their participation in the workplace could contribute to the national economy, while restoring their dignity and social integration. The United Nations Convention on the Rights of Persons with Disabilities (CRPD) entered into force on 3 May 2008. The CRPD is the first international legally binding treaty aimed specifically at protecting the rights of PWDs. It is expected of ratifying States Parties to either amend their domestic existing laws or to enact new legislation in order to meet their obligations, as set out in the CRPD. In 2008, South Africa ratified the CRPD and the Optional Protocol, thus committing itself to the provisions relating to, inter alia, workplace integration. Article 26 of the Convention mandates States Parties to take effective and appropriate measures to enable PWDs to attain and maintain maximum independence, physical, mental, social and vocational ability, and to ensure their social inclusion. Article 27 stipulates, inter alia, that States Parties shall safeguard and promote the realisation of the right to work, including those who incur a disability during the course of employment. Legislation should make provision for, inter alia the following: • enable PWDs to have effective access to general technical and vocational guidance programmes; • placement services and continued vocational training; • promote employment opportunities and career advancement; • assistance in sourcing, obtaining, maintaining and returning to work; and • reasonable accommodation in the workplace as well as vocational and professional rehabilitation. Although the Compensation for Occupational Injuries and Diseases Act 130 of 1993 was amended recently to include rehabilitation, re-integration and return to work (RTW) as part of its objectives, it will be argued that South Africa needs to initiate targeted legislation and policies that make disability management functions mandatory. Employers’ obligations need to be set out clearly in the Act, because, as it stands, the following lacunae exist: • There is no obligation to appoint Case Managers; • Dismissal protection is not provided for; • The regulation of negative incentives to assist with RTW compliance is lacking; and • The roles of different stakeholders in the RTW process require clarification. Without South Africa having an appropriate and detailed RTW framework, ill or injured employees stand the risk of losing their jobs and becoming dependent on family members and/or disability grants. Against this background, a comparative analysis of international and regional law and the RTW practices of two foreign jurisdictions were made. This enabled the author to devise recommendations and identify the roles of the government, employers, employees and Case Managers. The primary objective of this thesis is to determine how and to what extent regional and international standards and RTW programmes in other countries could assist in developing and amending the current legislative and policy framework in South Africa to promote the RTW of disabled employees.
Keywords: Disability management; Persons with Disabilities; Re-integration; Rehabilitation; Return to work

Portability of social security benefits of circular migrant workers in selected SADC member states - Masoebe, P. (North-West University, 2020)
The issue of portability of social security benefits is a daunting issue facing migrant workers in both Southern Africa and the world in general. In the Southern African Development Community region migration seems to be driven mainly by the need to attain economic freedom. The fact of the matter is that migrant workers from Lesotho and Swaziland who work and have worked in South Africa do play a major role in boosting these countries’ economies. Another issue that cannot be ignored is the fact that circular migration as a phenomenon is unlikely to come to an end any time soon in this part of the world. This means that social security benefits of migrant workers and its portability should be an issue that is dealt with cautiously and speedily, especially in terms of looking at the millions of unclaimed social security benefits reported each year by social security funds and schemes in South Africa. While examining the extent to which selected SADC member states, namely Lesotho, Swaziland and South Africa, have undertaken to combat this issue, international and regional instruments that have a bearing on social security rights are analysed and the realisation is that in as much as these do provide for social security rights and portability of benefits thereof, a lack of ratification and implementation play a vital role in achieving efficient portability of these rights. Although South Africa, as the largest migrant-receiving country in the SADC region, does provide for the right to social security in its Constitution, the fragmented nature of its social security framework, together with other factors such lack of information, exploitation by employers, distances travelled to lay claims and a non-existent social security adjudication system means that migrant workers are normally left with lack of redress when their contracts of employment reach an end. On the other hand, Swaziland and Lesotho, as migrant-sending countries, do not even have provisions in their constitutions that specifically deal with the right to social security. This means that citizens who work abroad do not have sufficient social security coverage in either country, as well as in South Africa as a host country. Consequently, multilateral and bilateral agreements on social security are pivotal in addressing this issue of unclaimed social security benefits as they go a long way in making sure that migrant workers are provided with adequate social security protection and coverage as a whole. Migrant sending countries also need to undertake unilateral initiatives to guarantee that their citizens are adequately protected in this specific sphere of social security. Examples are further drawn from the best practices of different regions in the world, namely the Southeast Asian Nations Region, Caribbean Community and Common Market and the Southern Common Market. The above-mentioned regions have established multilateral social security agreements that seek social security protection for migrant workers who play an undeniable role in their economies. Bilateral social security agreements between Zambia and Malawi, together with the one between Sweden and Philippines, are taken into consideration as best practices that Lesotho, Swaziland and South Africa may draw examples from when drawing up and concluding their own bilateral social security agreements. The Philippines’ unilateral initiatives are also discussed and hailed as the best practices that migrant-sending countries such as Lesotho and Swaziland may further draw examples from. The Philippines has developed strategies aimed at guaranteeing social protection for its migrant workers abroad and further makes sure that it enters into bilateral agreements with any country that receives services from its citizens. While the need to conclude multilateral and bilateral agreements on social security cannot be denied, there is also a need for migrant-sending countries to come up with unilateral initiatives to lessen the burden on migrant-receiving countries in this social security domain. Sectors such as the mining sector should also have mining-specific agreements that specifically deal with issues related to migrant mine workers. Lack of statistics of migrant workers moving in and out of South Africa has also been labelled as one of the reasons halting access and portability of social security benefits; hence there is a need to develop a data-base aimed at keeping track of all migrant workers, retired and otherwise. Migrant workers who seek redress regarding access of their unclaimed or unpaid social security benefits also have to be provided with comprehensive protection from the courts of law. This therefore means that an adjudication system should be established to deal with social security woes so that those seeking redress have adequate legal support.
Keywords: Labour and social protection; Migrant workers; Multilateral agreements; SADC; SADEC; Social protection; Social security; Sécurité sociale; Travailleur migrant